The commercialization of TV news an analysis of local TV news casts and audience perception of TV news commercialization - Agustin, Roshena Lenore Martinez
This study is a content analysis of five local TV newscasts namely TV Patrol (ABS-CBN 2), Pangunahing Balita (PTV-4), Balitang Balita (ABC-5), Saksi (GMA-7), and Newswatch the Evening Cast (RPN-9), and a survey of TV news audiences. Through content analysis, the study aimed to determine if there is profit-orientation or the so-called commercialization among TV newscasts, and if so, how is this manifested among local TV news programs. The survey, on the other hand, was aimed at determining the audiences' perception of TV news commercialization. Results of the content analysis revealed that the profit-orientation or orientation towards achieving greater revenues is manifested among local TV news programs in their news content and the length of time alloted by these news programs to advertisements. There is a significant dominance of political and crime stories. There is also a considerably long running time alloted by some newscasts to advertisements sponsoring these news programs. News is delivered fast as shown by the number of news items accomodated within the limited time alloted for news content. Results of the survey showed that TV news audiences are highly aware of TV news commercialization. It also showed that majority of the respondents are against the commercialization of TV news while there is a significant number of TV news viewers who are neutral. An interesting finding, however, is that despite this attitude towards commercialization, majority of the respondents still prefer watching TV Patrol and Saksi. These two are the two most highly commercialized newscasts, based on the observation made in this study. These findings have both positive and negative implications. While it may lead to further improvement of the quality of TV newscasts, commercialization of TV news, on the other hand, increases the potential of turning news programs as mere marketing tools rather than a public service oriented organization. Thus it is recommended that vigilance be observed as to when media economics overshadows TV news programs' responsibility to serve.